Audio-visual advertisement: looking at the law / Fairos Danial Mazlan, Anisha Liza Mohd Sharidan and Afidah Nor Ariffin - Mazlan, Fairos Danial; Mohd Sharidan, Anisha Liza; Ariffin, Afidah Nor (2005)
In section 3(3) of Communication and Multimedia Act 1998, the provision stated that in Malaysia, the internet cannot be censor. This provision showed that Malaysia has approved the advertisement in the internet can not be control. People around the world can advertise their product in Malaysia easily on the internet. Under section 9 of Broadcasting Act stated that any broadcast come from outside country must get approval from the minister. However in this it doesn't state the definition of broadcasting. This provision was actually was not applicable in Malaysia because there are still advertisement which been banned after it been published. Those two provisions have some lacking; it is when it comes to the broadcasting in the internet. The internet cannot be censored but the broadcasting act stated that any broadcast should get the approval from the minister. Freedom of expression that been stated in article 10 of Federal Constitution were saying that every citizen have the right of expression. However we cannot determine whether this article includes the audio-visual advertisement or all kind of advertisement. There are no specific provisions for the audio-visual advertisement in Malaysia. It shows that broadcasting is not important for government.